Determinants of Host Range Specificity in Legume-Rhizobia Symbiosis - Walker, Liam; Lagunas, Beatriz; Gifford, Miriam L. (Frontiers in Microbiology, 2020)
Leguminous plants possess the almost unique ability to enter symbiosis with soil-resident, nitrogen fixing bacteria called rhizobia. During this symbiosis, the bacteria physically colonize specialized organs on the roots of the host plant called nodules, where they reduce atmospheric nitrogen into forms that can be assimilated by the host plant and receive photosynthates in return. In order for nodule development to occur, there is extensive chemical cross-talk between both parties during the formative stages of the symbiosis. The vast majority of the legume family are capable of forming root nodules and typically rhizobia are only able to fix nitrogen within the context of this symbiotic association. However, many legume species only enter productive symbiosis with few, or even single, rhizobial species or strains and vice-versa. Restricting symbiosis to only strains which will result in nitrogen fixation with high efficiency is a crucial strategy for the host plant to prevent cheating by rhizobia. This selectivity is enforced at all stages of the symbiosis, with partner choice beginning during the initial communication between the plant and rhizobia. However, it can even be influenced once nitrogen-fixing nodules are present and colonized on the root. This review sets out current knowledge about the molecular mechanisms employed by both parties to influence host range during nodulation.